Академічна доброчесність: практичний досвід. Вип. 4 - Хмельницький інститут ПрАТ «ВНЗ «МАУП» (My University, 2023)
У збірнику наукових праць вміщено статті та тези виголошені на науково-практичному семінарі «Академічна доброчесність: шлях до забезпечення якості освіти», що відбувся у Хмельницькому інституті МАУП 19 жовтня 2023 року. The collection of scientific papers contains articles and theses presented at the scientific and practical seminar "Academic Integrity: The Path to Ensuring the Quality of Education", which was held at the Khmelnytsky Institute of the IAPM on October 19, 2023.